Board of Editor - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Board of Editor PATRON: Dean - Faculty of Civil, Environmental, Earth Sciences - ITS.Head Training Center Management & Functional Position - Ministry of PWPH. RESPONSIBLE : Head of Department – Civil Engineering Department - ITSBOARD OF EDITOR Chief Editor : Hitapriya Suprayitno ITS, Indonesia h-index (GS = 8)Editor : Ria Asih Ariyani Soemitro ITS, Indonesia h-index (GS = 9) Data Iranata ITS, Indonesia h-index (GS = 3) Alex Abdi Chalik PUPR, Indonesia h-index (GS = ) Danang Parikesit UNIID, Indonesia h-index (GS = 7) Maimunah Sapri UTM, Malaysia h-index (GS = 14) Address : Editor JIFAM – Room J - 201 Departement of Civil Engineering Institut Teknologi Sepuluh Nopember ITS Campus, Sukolilo, Surabaya 60111 Email: jurnal.jifam@gmail.com Website: https://iptek.its.ac.id/index.php/jifamReviewer for this EditionRia Asih Aryani Soemitro, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, Indonesia.Data Iranata, Institute of Technology Sepuluh Nopember (ITS), Surabaya, Indonesia.Caroline Sutandi, Universitas Parahyangan, Bandung, Indonesia.Eko Budi Santosa, Instiute of Technology Sepuluh Nopember (ITS), Surabaya, Indonesia.Akhmad Wicaksono, University of Brawijaya, Malang, Indonesia.Hitapriya Suprayitno, Insitute of Technology Sepuluh Nopember (ITS), Surabaya, Indonesia.